Hubungan Karakteristik Petani dan Modal Sosial dengan Keberdayaan Petani Nilam di Kabupaten Togo Una-Una, Sulawesi Tengah - Managanta, Andri Amaliel; Ridwan; Laopa, Firda; Ahmad, Nurmayanti H (Analisis Kebijakan Pertanian, 2025)
ABSTRACT Patchouli is a plant with promising potential and high market demand. The high selling price of patchouli oil has an excellent opportunity to increase farmers’ income. However, the high demand for this product is also accompanied by low productivity, weak farmer empowerment, and low social capital. This condition shows the importance of the role of social capital in farmers’ empowerment. This study aimed to analyze the relationship between farmers’ characteristics and social capital with the level of farmers’ empowerment of farmers. Data collection was done by a survey carried out in Malenge Village, Tojo Una-Una Regency, Central Sulawesi, from May to December 2021. The number of respondents was 97 farmers and was chosen by a simple proportional sampling technique. The data were analyzed using the Spearman Rank correlation test to examine the relationship between farmer characteristics and social capital with their level of empowerment. Farming motivation and cosmopolitan level play a role in increasing farmer empowerment and beliefs and norms or customary rules that guide farming. The motivation and curiosity increase of farmers outside the social system can improve farmers’ ability in the marketing process, farm productivity, and procurement of production facilities. One of the important efforts to empower patchouli farmers is by increasing the role of extension workers who actively assist and provide information according to the needs of farmers.